New strategies for the production of butanol and 1,3-propanediol from glycerol - Gallardo, R. (2013)
The increasing demand for use of renewable resources as feedstock for the production of chemicals combined with advances in biotechnology is generating a renewed interest in the fermentative production of n-butanol and 1,3-propanediol (1,3-PDO). In this context, glycerol, a by-product of biodiesel and ethanol production, arises as a potential substrate for this purpose. In this work, Clostridium pasteurianum DMS 525 was studied for butanol production using biodiesel-derived crude glycerol and pure glycerol as the carbon source. The main products obtained were butanol and 1,3-PDO. Moreover, the competitive nature of butanol and 1,3-PDO pathways was evident, and a shift to the former for higher glycerol concentrations was clearly observed. In preliminary experiments conducted in serum bottles using crude glycerol, the maximum glycerol consumption achieved was 31.83 ± 0.98 g l-1, which resulted in 6.71 ± 0.42 g l-1 of butanol and 6.86 ± 0.51 g l-1 of 1,3- PDO. To improve the butanol tolerance of C. pasteurianum DSM 525, random chemical mutagenesis (N-ethyl-N-nitrosourea) in solid medium was performed. Experiments resulted in the isolation of colonies growing in culture medium containing 12 g l-1 butanol (except in the controls). Mutant cells showed 20 % higher butanol production than the parent strain when grown in liquid medium. Optimization of the culture medium composition and the inoculum age resulted in a glycerol consumption and a butanol titer of 45.62 ± 3.81 g l-1and 12.4 ± 0.26 g l- 1, respectively. The concentration of 1,3-PDO reached 7.45 ± 0.86 g l-1. In particular, iron was found to play a key role in this process. Supplementation of 3 mg l-1 FeCl2.7H2O in the culture medium led to 140% increase in butanol titer. In pH-controlled experiments, it was possible to increase glycerol consumption to a maximum of 75 g l-1. Nevertheless, butanol production was around 9 g l-1and higher concentrations of 1,3-PDO were obtained (20 g l-1). Finally, the production of 1,3-PDO was studied in continuous culture (EGSB reactors). Two pre-treatments (heat and disruption) were applied to the granular sludge in order to minimize the methane production. 1,3-PDO was always found to be the main product and only small amounts of acids were detected. Molecular biology tools (DGGE, cloning and sequencing) were used to evaluate the microbial community. A maximum 1,3-PDO yield and productivity of 0.43 g g-1 and 57 g l-1d-1, respectively, were achieved in the reactor operated with nontreated granular sludge (control). The results obtained provide a deeper understanding of a complex process such as the anaerobic fermentation of glycerol using Clostridium spp. C. pasteurianum shows a great potential for butanol and 1,3-PDO production from crude glycerol. However, butanol toxicity seriously limits its titer, thus it is important to find ways to overcome this problem. On the other hand, this study proves the feasibility of 1,3-PDO production in EGSB reactors, which have the advantage of being operated under non-sterile conditions and represent a novel strategy to valorise glycerol generated as by-product in the biodiesel industry.